Incidence, Outcome and Predictors of Mortality in Respiratory distress syndrome (RDS): A Prospective Cohort Study at Tertiary Care Hospital in Nepal: - Basnet, Srijana; Aryal, Surabhi; Shrestha, Laxman (Journal of Nepal Paediatric Society, 2022)
Introduction: With advances in therapies during antenatal and perinatal period, there has been apparent decrease in incidence and mortality due to respiratory distress syndrome (RDS). However, there is paucity of data on exact incidence and outcome of RDS in resource limited setting. This study was conducted with the primary aim to describe the outcome of RDS and analyze the predictors for mortality. Methods: A prospective observational study was conducted in the Neonatal Intensive Care Unit (NICU) and Neonatal Unit of Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal from October 2019 to April 2021. Results: A total of 94 preterm newborns developed RDS giving prevalence of 20.5 per 1000 live birth cohort at TUTH. Incidence of RDS among preterm babies was 14.6%. The median duration of continuous positive airway pressure (CPAP) was 48 hours (Range 8 - 192 hours). Inhospital mortality rate was 15 (15.96%). Lower gestational age and premature rupture of membrane (PROM) were significantly associated with higher mortality whereas Normal Vaginal delivery (NVD) was associated with lower mortality. Logistic regression analysis for risk of dying for the cohort predicted that lower birth weight (AOR = 0.99; 95% CI = 0.99 - 0.99; P = 0:01), sepsis (AOR = 145.14; 95% CI = 5.04 - 4175.15; P = 0:004) are independently associated with increased risk of dying whereas increase duration of NICU stay decreased the risk (AOR = 0.71; 95% CI = 0.54 - 0.91; P = 0:01). Conclusions: The mortality rate decreases with increasing gestational age and birth weight. A number of neonatal factors, either in isolation or in combination, were significantly associated with in-hospital mortality